Komparasi Pengawasan Bisnis Bank Digital Dan Bank Konvensional Berdasarkan Peraturan Perbankan Di Indonesia - Laksono, Arifin Pringgo; Saputro, Candra Wahyu; Putra, Ega Kesatrya (Technology and Economics Law Journal, 2024)
Digital transformation in Indonesia's banking industry has created new opportunities and challenges for the national financial system. The increase in digital banking transactions is supported by digital economic growth of USD 90 billion, reflecting significant changes in consumer preferences and banking structures. However, this pace of development has been accompanied by a 50% increase in cybersecurity incidents from 2021 to 2023, threatening public trust and financial system stability. Regulations set by the Financial Services Authority (OJK) through POJK No. 12/POJK.03/2021 and POJK No. 12/POJK.03/2018 have attempted to accommodate the needs of digital banks, but challenges in technology oversight, cybersecurity, and cross-border compliance remain significant. Regulations issued by the Financial Services Authority (OJK) through POJK No. 12/POJK.03/2021 and POJK No. 12/POJK.03/2018 have attempted to accommodate the needs of digital banks, but challenges in technology supervision, cybersecurity, and cross-border compliance remain significant. This study uses a normative legal method with a legislative and comparative approach. The results show fundamental differences in the supervision of digital banks and conventional banks, where digital banks place more emphasis on technology-based supervision such as RegTech and SupTech, while conventional banks use traditional methods that focus on asset quality and credit risk management. There is no difference in the sanctions imposed on digital and conventional banks, but the sanctions are adjusted to the type of violation and the form of operational activities. A comparison with ASEAN countries such as Singapore, Malaysia, and Thailand shows that Indonesia's supervisory framework still needs to be strengthened, especially in the adoption of supervisory technology to address risks and support innovation. This study concludes that banking supervision must be adaptive to technological developments to maintain financial stability and inclusion in the digital era.